Spatially differentiated impacts of Covid-19 on selected indicators of mortality in Slovakia in 2020 - Michálek, Anton (Geographica Pannonica, 2022)
Slovakia is a country with a specific development of the Covid-19 pandemic. While it was among the countries with the lowest number of cases and lowest mortality during the first wave, during the second and third waves Slovakia gradually became one of the countries with the worst development of the pandemic. The aim of this contribution is to summarise the situation in Slovakia during the first year of the pandemic and investigate its influence on selected indicators of mortality. An attempt was also made at determining its influence on the lethality rate of Covid-19, changes in mortality, and excess deaths. The research considered regionally differentiated levels and identification of risk districts from the aspect of the abovementioned phenomena.